World Englishes--problems, properties and prospects : selected papers from the 13th IAWE conference - Hoffmann, Thomas, 1976-; Siebers, Lucia (Varieties of English around the world. General series, 2009)
World Englishes is a vibrant research field that has attracted scholars from many different linguistic subdisciplines. Emphasizing the common ground of all research on World Englishes, the 22 articles in this collected volume, selected from more than a hundred papers presented at the 2007 conference of the International Association for World Englishes in Regensburg, cover a broad range of topics which together reflect the state of the art of research in this field. The volume focuses on regions as diverse as Africa, the Caribbean, the Antipodes and Asia, but also promotes a globally comparativ.